Testing the role of independent supervisory board characteristics on the relationship between earnings management and quality of corporate social reporting disclosure - Widyaniandhita, La-Dibba Aulia; Solihin, Mahfud (Journal of Contemporary Accounting, 2020)
This research aims to examine whether a company with high earnings management discloses high quality Corporate Social Reporting (CSR) information to obscure the stakeholders’ view related to earnings management practice within the company. The characteristics of independent supervisory board as formal supervisor is predicted to weaken the relation between earnings management and quality of CSR disclosure. Using Thompson Reuters and Osiris databases, 242 samples consist of 36 companies from 5 countries, namely Indonesia, Malaysia, Singapore, Thailand and Philippines were obtained. The results show that the proportion of independent supervisory board has negative role in moderating the relationship between earnings management and quality of CSR disclosure. The larger the proportion of independent supervisory board, the more effective the supervisory board in conducting supervision so the earnings management decreases. Companies with low earnings management do not have tendency in disclosing the CSR information with better quality as an effort to obscure the earnings management, so CSR information is revealed truthfully or even lower than expected.